How to increase your chances of obtaining a significant association between handedness and disorder. - Bishop, D (1990)
Handedness inventory data are peculiarly prone to be used to classify subjects in a post hoc fashion. Data from a computer simulation are used to show that if this procedure is adopted, significance levels can be seriously misleading: under certain conditions the odds of obtaining "significant" results by chance are as high as 2:3. Specification of cutoffs after inspection of the data is probably the most important source of spurious associations between handedness and disorder.